Hubungan Aktivitas Fisik, Kecukupan Energi dan Lemak dengan Obesitas Abdominal pada Mahasiswa Universitas Pendidikan Indonesia: Correlation of Physical Activity, Energy and Fat Sufficiency with Abdominal Obesity in Students at Universitas Pendidikan Indonesia - Anggraeni, Nuri; Rosdiana, Delita Septia; Astuti, Widya; Fauza, Ahdiyatul (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
Abdominal obesity is one of the most sensitive and accurate indicators for assessing a person's risk of developing degenerative diseases. College students are considered a vulnerable group as they are in a transitional phase toward adulthood, often experiencing lifestyle changes, irregular eating patterns, lack of physical activity, and high levels of stress due to academic demands. This study aims to identify the factors associated with abdominal obesity among students at Universitas Pendidikan Indonesia (UPI). This research uses a quantitative approach with a cross-sectional design. Based on the Lemeshow formula, the total number of subjects in this study is 41, with a 10% margin of error. The primary data used were obtained through two methods, interviews and anthropometric measurements. Data analysis includes univariate and bivariate tests. The bivariate analysis used is the chi-square test. The results of the study show a significant relationship between energy adequacy (p-value=0.02), fat adequacy (p-value=0.034), and physical activity (p-value=0.036) with the abdominal obesity.